Ultrafast electron transfer dynamics in lateral transition-metal dichalcogenide heterostructures. (13th September 2019) - Zheng, Zhenfa; Zheng, Qijing; Zhao, Jin
Abstract: The ultrafast charge transfer in vertically stacked van der Waals transition-metal dichalcogenide (TMD) heterostructures shows enormous value in the fields of optoelectronics and solar energy conversion. Compared to vertical TMD heterostructures, the lateral (in-plane) heterostructures have stronger interaction between different TMD materials due to the formation of covalent bonds, which is more conducive to charge transfer. To understand the charge transfer dynamics in lateral TMD heterostructure, we employ ab initio nonadiabatic molecule dynamics to simulate the photoexcited electron transfer in lateral MoS2 /WS2 heterostructure. Our study shows that the type-II band alignment can be formed in MoS2 /WS2 at zero temperature. However, because the band offset of valence band maximum (VBM) is as small as 0.1 eV, the VBM of MoS2 and WS2 cross each other frequently when the temperature is increased to 100 or 300 K. In these cases, the phonon excitation destroys the type-II band alignment and makes the hole transfer to be difficult. By contrast, the band offset of conduction band minimum is kept with phonon excitation and our investigation shows that the electron transfer can happen in an ultrafast manner and the dynamics are independent of the interface structures. Comparing with the vertical MoS2 /WS2 heterostructure, the nonadiabatic electron transfer can happen faster in lateral heterostructure because of the stronger orbital hybridization. Our investigation on lateral MoS2 /WS2 heterostructures provide unique insights into the ultrafast charge transfer dynamics at lateral TMD interface at atomic scale, which have potential applications for the design of novel 2D devices for optoelectronics and clean energy.